RAISING OF STOCKING MATERIALS IN PEN ENCLOSURE IN A FLOODPLAIN WETLAND OF UTTAR PRADESH - DAS, SC S; ALAM, ABSAR; JHA, D N; KUMARI, V; SRIVASTAVA, K; BHATTACHARJYA, B K (Journal of the Inland Fisheries Society of India, 2021)
An experiment was conducted in Alwara taal of Uttar Pradesh, India to rear Indian major carp fry in pen enclosure during 2014-15 for production of stocking materials. A rectangular off-shore all-net pen covering 0.125 ha area was installed in the wetland using HDPE screens (5 mm mesh size), nylon webbing (5 mm mesh size), foot rope (3 mm diameter) bamboo poles and twines. The pen was stocked with advance fry of Catla catla, Labeo rohita and Cirrhinus mrigala @ 20 nos. m-2 in the ratio of 2:1:1 The stocked fishes were fed with supplementary feed @ 2-5% of their body weight giving overall FCR value of 1.11. Catla, rohu and mrigal fry grew from 6.85 g ±0.48, 3.77 g ± 0.31 and 5.03 g ± 0.26 to 123.10 g ± 5.53, 85.4 g ± 4.91 and 72.3 g ± 2.42 in 110 days culture period. The specific growth rate and survivality (%) of reared fishes were: 2.62 and 61.2% for catla, 2.84 and 66.3% for rohu whereas these were 2.42 and 68.2% for mrigal. Mean values of important water quality variables like transparency (35 cm), pH (7.5), total alkalinity (212 mg l-1), total hardness (178 mg l-1), dissolved oxygen (6.3 mg l-1), phosphate-P (0.072 mg l-1) and nitrate-N (0.09 mg l-1) indicated that the wetland was suitable for pen aquaculture. Benefit-cost ratio and return on investment were 1.53 and 0.53 indicating that pen aquaculture was economically viable for rearing of carp advance fry to fingerling stage in floodplain wetlands of Uttar Pradesh. Key words: Pen aquaculture, floodplain wetlands, Alwara taal, FCR, benefit-cost ratio